2021
DOI: 10.21608/adjc.2021.86807.1103
|View full text |Cite
|
Sign up to set email alerts
|

Thermocycling Effect on Implant Supported Overdenture Using 3D printed Peek Bar following all-on-4 Concept: Randomized Trial-In vitro Study

Abstract: Objective: Stress analysis and retention evaluation of implant-retained mandibular complete overdenture with different clip materials and distributions. Methods: This in-vitro study was conducted over implants retained mandibular complete overdenture (all-on-4 concept) using BIOHPP bar attachments constructed using 3 D printing with different clip materials and distributions. This study consisted of 4 groups according to the type and distribution of clips: Group I: hard clips anteriorly and posteriorly, Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…However, the rest of the aspects showed no significant difference. The crestal bone loss that occurred during the follow up period may be due to surgical trauma during drilling, the remodeling process post implant insertion and/or due to occlusal loading (35,36) The present study's results revealed that; there was a gradual increase in the maximum biting force in patients rehabilitated by implant overdentures in the two studied groups throughout study period. This finding may be due to many reasons; the gradual rise in the maximum bite force may be due to the neuromuscular co-ordination and adaptability of the patient to the prostheses upon time; however it was reported that implant supported prostheses may restore the oral function successfully, both subjective and objective indicators of chewing ability score better compared to conventional complete dentures; more over the refined stability and retention provided by the implants may have lowered patient's fear and promoted them to exert higher biting force.…”
Section: Discussionmentioning
confidence: 55%
“…However, the rest of the aspects showed no significant difference. The crestal bone loss that occurred during the follow up period may be due to surgical trauma during drilling, the remodeling process post implant insertion and/or due to occlusal loading (35,36) The present study's results revealed that; there was a gradual increase in the maximum biting force in patients rehabilitated by implant overdentures in the two studied groups throughout study period. This finding may be due to many reasons; the gradual rise in the maximum bite force may be due to the neuromuscular co-ordination and adaptability of the patient to the prostheses upon time; however it was reported that implant supported prostheses may restore the oral function successfully, both subjective and objective indicators of chewing ability score better compared to conventional complete dentures; more over the refined stability and retention provided by the implants may have lowered patient's fear and promoted them to exert higher biting force.…”
Section: Discussionmentioning
confidence: 55%
“…In an invitro investigation over implants held mandibular complete overdentures (all-on-4 concept) utilizing BioHPP and metal bar attachments, it was discovered that after thermocycling, the retention force of BioHPP bar attachment was much higher than the retention force of metal bar attachment. The BioHPP bar attachment overdentures may be a preferable choice for patients looking for greater retention force and resilience to cyclic loading 14 The bars in implant overdentures are conventionally constructed utilizing the lost-wax method casting method, which is labor-intensive and time-consuming. Construction of one-piece casted bar attachment are frequently faced with difficulties such as probable porosities and misfits 15 .…”
Section: Mandibularmentioning
confidence: 99%